Traditional knowledge on zootherapeutic uses by the Saharia tribe of Rajasthan, India - Jaroli DP; Mahawar Madan (BMC, 2007)
Abstract The present zootherapeutic study describes the traditional knowledge related to the use of different animals and animal-derived products as medicines by the Saharia tribe reside in the Shahabad and Kishanganj Panchayat Samiti's of Baran district of Rajasthan, India. A field survey was conducted from April to June 2006 by performing interview through structured questionnaire with 21 selected respondents, who provided information regarding use of animals and their products in folk medicine. A total of 15 animal species were recorded and they are used for different ethnomedical purposes, including cough, asthma, tuberculosis, paralysis, earache, herpes, weakness, muscular pain etc. The zootherapeutic knowledge was mostly based on domestic animals, but some protected species like the peacock (Pavo cristatus,), hard shelled turtle (Kachuga tentoria), sambhar (Cervus unicolor) were also mentioned as medicinal resources. We would suggest that this kind of neglected traditional knowledge should be included into the strategies of conservation and management of faunistic resources. Further studies are required for experimental validation to confirm the presence of bioactive compounds in these traditional remedies and also to emphasize more sustainable use of these resources.